DEVELOPMENT OF ANIMATED LEARNING VIDEOS ON THE FOOD MATERIALS FROM POULTRY - Widi Handayani, Titin Hera; Pringgodani, Satria Sidiq (Home Economics Journal, 2024)
The objectives of this research are: 1) to develop animated video learning media on poultry food and its processed products, 2) to determine the feasibility of animated videos. This is a type of Research and Development with a 4D model: 1) define: collect information about the curriculum and syllabus used, 2) design: development design which includes the pre-production stage, namely compiling material, making story boards, validating scripts and forming a team in making animated videos, 3) develop: implement the storyboard that has been made into an animated video, then the presentation video is tested for suitability by media and material experts. Next, it was tested on potential users, 4) dissemination: product distribution at SMKN 2 Godean to teachers and students of class X Catering. The small-scale research subjects were 6 students and the large-scale research subjects were 30 students. The data collection technique uses a questionnaire. Data analysis is quantitative descriptive. The results are: 1) research development procedures using a 4D research model to produce animated learning video products, 2) research data obtained: a) material experts 96.72%, b) media experts 96.01%, c) small scale trials 85, 58 %. d) large-scale trials 82.40%, all trials received the "Very Feasible" category.